Evaluasi Model CIPP Dalam Program Pendidikan Kesetaraan Paket B di PKBM Abdi Pertiwi - Putri P., Christina Pricilia; Dwiwanda, Nabila Putri; Rarameha, Rambu Mutiara (Program Studi Pendidikan Luar Sekolah, 2024)
Abstract: This study aims to describe the level of effectiveness of the implementation of the B equivalency package education program at PKBM Abdi Pertiwi by using the CIPP (context, input, process, product) evaluation model. This study is an evaluative research that applies the CIPP evaluation model as an approach. Techniques and data collection of this study used interviews and direct observation methods. The sampling technique used Non-probability sampling technique. From the results of the study, it can be seen that the level of effectiveness of the context, input, process, and product components is considered very effective in accordance with the established criteria. The input aspect of the package B equivalency education program at PKBM Abdi Pertiwi is in the category of good enough to see from the selection of tutors who are not too strict and rigid. While looking at the Process aspect, it is in the very good category, it can be seen from the learning schedule which is determined by agreement between tutors and students. It can be concluded that the effectiveness of the CIPP Model Evaluation in the Package B Equivalency Education Program at PKBM Abdi Pertiwi is considered very effective.Key Words: Evaluation, Program, CIPP Model, Equality Education, PKBMAbstrak: Penelitian ini bertujuan untuk mendeskripsikan tingkat keefektifan pelaksanaan program pendidikan paket kesetaraan B di PKBM Abdi Pertiwi dengan menggunakan evaluasi model CIPP (context, input, process, product). Studi ini merupakan penelitian evaluatif yang menerapkan model evaluasi CIPP sebagai pendekatan. Teknik dan pengumpulan data penelitian ini menggunakan metode wawancara dan observasi langsung. Teknik pengambilan sampel menggunakan teknik Non-probability sampling. Dari hasil penelitian, terlihat bahwa tingkat efektivitas komponen konteks, input, proses, dan produk dinilai sangat efektif sesuai dengan kriteria yang ditetapkan. Adapun aspek Input program pendidikan kesetaraan paket B di PKBM Abdi Pertiwi masuk dalam kategori cukup baik melihat dari penyeleksian tutor yang tidak terlalu ketat dan kaku. Sedangkan melihat dari aspek Proses nya masuk dalam kategori sangat baik dapat dilihat dari jadwal pembelajarannya yang ditetapkan melalui kesepakatan antara tutor dan peserta didik. Dapat disimpulkan efektivitas Evaluasi Model CIPP dalam Program Pendidikan Kesetaraan Paket B di PKBM Abdi Pertiwi dinilai sangat efektif.Kata Kunci: Evaluasi, Model CIPP, Pendidikan Kesetaraan, PKBM, Program.